1985
DOI: 10.1111/j.1476-5381.1985.tb11105.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of recovery of gastric epithelial integrity by 16,16‐dimethyl prostaglandin E2

Abstract: The effects of pretreatment with 16,16‐dimethyl prostaglandin E2 (DmPGE2) on the recovery of gastric mucosal ‘barrier’ parameters after ethanol‐induced damage were studied using an ex vivo chamber preparation in the rat. DmPGE2 (4–40 μg kg−1) significantly reduced the extent of haemorrhagic damage to the gastric mucosa induced by the topical application of 50% ethanol followed by 0.05 M hydrochloric acid. The lowest dose of DmPGE2 tested (4 μg kg−1) had no effect on the ethanol‐induced changes in transmucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It has been shown that exogenously ad ministered PGs significantly accelerate the recovery of the epithelial integrity in the rat stomach after exposure to 50 or 100% etha nol [18,19], The present study confirmed the above findings and further showed that endogenous PGs may be involved in the cel lular events associated with the mucosal res toration. Indomethacin, a cyclooxygenase inhibitor, delayed the recovery of PD after exposure to 50% ethanol, and this effect was completely reverted by concurrent adminis tration of 16,16-dmPGE2.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that exogenously ad ministered PGs significantly accelerate the recovery of the epithelial integrity in the rat stomach after exposure to 50 or 100% etha nol [18,19], The present study confirmed the above findings and further showed that endogenous PGs may be involved in the cel lular events associated with the mucosal res toration. Indomethacin, a cyclooxygenase inhibitor, delayed the recovery of PD after exposure to 50% ethanol, and this effect was completely reverted by concurrent adminis tration of 16,16-dmPGE2.…”
Section: Discussionsupporting
confidence: 80%
“…1, 2 Indeed, prostaglandins have been shown to be important mediators of epithelial restitution in the stomach, 28,29 and their importance in repair of ulcers is underscored by the marked ability of NSAIDs to interfere with this process. 30,31 While it is now clear that there are at least two isoforms of cyclooxygenase (the principle enzyme responsible for prostaglandin synthesis), the relative contribution of each isoform to mucosal prostaglandin synthesis in various circumstances is not clear.…”
Section: Discussionmentioning
confidence: 99%